Rectal polyposis in mucosal prolapse syndrome - Wong, Yin Ping; Kabincong, Connie; Jabar, Mohd Faisal; Tan, Geok Chin (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Mucosal prolapse syndrome is also known as solitary rectal ulcer syndrome. It may either presents as an ulcer or polyp, which could mimic other pathological lesions such as juvenile polyp, hyperplastic polyp, adenomatous polyp, polyp related inflammatory bowel disease and adenocarcinoma. It can pose as a diagnostic challenge to both the surgeons and pathologists due to the overlapping gross and histological features. The characteristic histological features of mucosal prolapse syndrome are fibromuscular obliteration of lamina propria and splayed hypertrophic muscularis mucosae. It can occur in a wide range of ages, including children and teenagers. Rectal bleeding is one of the common presenting symptoms. Here, we described two cases of mucosal prolapse syndrome presented as rectal polyposis and provide a discussion on its histological differential diagnosis.